2011
DOI: 10.3389/fpsyg.2011.00059
|View full text |Cite
|
Sign up to set email alerts
|

Hand in Motion Reveals Mind in Motion

Abstract: Recently, researchers have measured hand movements en route to choices on a screen to understand the dynamics of a broad range of psychological processes. We review this growing body of research and explain how manual action exposes the real-time unfolding of underlying cognitive processing. We describe how simple hand motions may be used to continuously index participants’ tentative commitments to different choice alternatives during the evolution of a behavioral response. As such, hand-tracking can provide u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
289
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(298 citation statements)
references
References 36 publications
9
289
0
Order By: Relevance
“…Participants completed a computer-based multiple-choice version of the CRT while their mouse cursor movements were recorded. Mouse tracking has been used in other areas of psychology to reveal the time course of decisions on the basis of participants' mouse cursor trajectories over a short period of time (Freeman, Dale, & Farmer, 2011;Spivey, Grosjean, & Knoblich, 2005). We employ it here to capture the cognitive processing underlying CRT performance over a longer timescale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed a computer-based multiple-choice version of the CRT while their mouse cursor movements were recorded. Mouse tracking has been used in other areas of psychology to reveal the time course of decisions on the basis of participants' mouse cursor trajectories over a short period of time (Freeman, Dale, & Farmer, 2011;Spivey, Grosjean, & Knoblich, 2005). We employ it here to capture the cognitive processing underlying CRT performance over a longer timescale.…”
mentioning
confidence: 99%
“…In previous mouse tracking research (e.g. Freeman et al, 2011;Spivey et al, 2005), recording movements over a few seconds, the cursor typically moves straight to a response option, curves between two of them, or in some cases moves to one, and then the other. In our data, unfolding over up to 60 seconds, participants move and rest the cursor many times The time course data also allow us to supplement the response time analyses reported above by looking at the speed at which participants moved the mouse cursor to the region of the response option they eventually did select.…”
mentioning
confidence: 99%
“…That is, trajectories for unit decade incompatible targets traced to the left of the trajectories for compatible targets. Such behavior cannot be explained by an embodiment view of two-digit number representation (Bloechle et al, 2015), and instead supports a model where decision dynamics stem from competition among parallel and partially active responses (Freeman, Dale, & Farmer, 2011). Of course, the present work is not sufficient to completely specify the architecture of such a model, so this will likely be an exciting future avenue for research.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, behavioral testing methodologies have been developed that place a stronger emphasis on the dynamics of the action-based components of RS (Duran, Dale, & McNamara, 2010;Spivey, Grosjean, & Knoblich, 2005). As one example, by tracking the streaming pixelcoordinate trajectories of computer-mouse movements as the cursor is moved to a presented stimulus, one can obtain an action-based index of the co-activation of stimulusresponse (S-R) alternatives representations (Freeman, Dale, Farmer, 2011;Song & Nakayama, 2006;Spivey et al, 2005;Magnuson et al, 2007). The continuous nature of the movement trajectories can provide more direct evidence for competition between response options that cannot be easily detected when reaction time (RT) is the primary measure (Eriksen & Eriksen, 1974;Kornblum, 1965;Miller, 1988Miller, , 1993.…”
Section: Computer-mouse Tracking and The Dynamics Of Response Selectionmentioning
confidence: 99%
“…Stated broadly, experimental results have consistently demonstrated that arm movements (as measured by the movement trajectories of the computer mouse or other devices) systematically reflect ongoing cognitive processes in a wide range of tasks (for reviews of this literature, see Freeman, Dale, & Farmer, 2011;Song & Nakayama, 2009). …”
Section: Computer-mouse Tracking and The Dynamics Of Response Selectionmentioning
confidence: 99%